МАТЕМАТИЧНА МОДЕЛЬ ВИСОКОВОЛЬТНОГО ЦИФРО-АНАЛОГОВОГО ПЕРЕТВОРЮВАЧА ДЛЯ РОЗРАХУНКУ СПОТВОРЕНЬ ВИХІДНОГО СИНУСОЇДАЛЬНОГО СИГНАЛУ - Тесик , Ю.Ф.; Мороз, Р.М. (Інститут електродинаміки НАН України, Київ, 2016)
Two simplified mathematical models for calculate the change in the output impedance and distortion sine wave output of the high-DAC for different types of switching reference sources are proposed. The advantages of the circuit with switching transistors by help of the mathematical modeling is provided. References 7, figures 8.